Prevalence and associated factors of last dental visit and teeth cleaning frequency in Bangladesh, Bhutan, and Nepal: Findings from nationally representative surveys. - Rajat Das Gupta; Shams Shabab Haider; Shah Saif Jahan; Md Irteja Islam; Ananna Mazumder; Muhammad Sohail Zafar; Nazeeba Siddika; Ehsanul Hoque Apu (Public Library of Science (PLoS), 2024)
This study evaluated the prevalence and frequency of teeth cleaning and last dental visits, along with associated socio-demographic factors, among residents of Bangladesh, Bhutan, and Nepal. The World Health Organization (WHO) STEPwise approach to surveillance (STEPS) survey data from Bangladesh (N = 8,164), Bhutan (N = 5,374) and Nepal (N = 5,371) were analyzed. After descriptive analysis, a multivariable multilevel logistic regression was conducted to identify the factors associated with oral hygiene. The following variables were considered as outcomes of interest: daily teeth cleaning frequency and visitation to the oral healthcare providers in the last six/twelve months at the time of data collection. Bangladesh had the highest proportion of respondents who cleaned their teeth at least once or twice a day, while Nepal had the lowest. Bhutan had the highest proportion of respondents who visited a dentist within the last six months (10.5%) or 12 months (16.0%). Almost 94.5% of Nepalese participants never visited a dentist. Participants of older age, who were females and had increased educational attainment, were more likely to follow oral hygiene measures. The populations of all the countries included in the study show poor adherence to oral hygiene practices. Health promotion programs should raise awareness regarding the advantages of regular teeth cleaning and dental check-ups.